(untitled) (Somma: Revista Científica do Instituto Federal do Piauí, 2025)
Anurans possess various defense mechanisms, including contracting, which aims to prevent injury during subjugation and hinder predation. Herein, we describe the defensive behavior of contracting in Rhaebo guttatus recorded in the Chapada das Mesas National Park, Maranhão, Brazil. On April 19, 2023, a juvenile male R. guttatus exhibited contracting behavior for approximately 27 minutes while being handled, before returning to normal activity. This is the first record of contracting behavior for R. guttatus. Contracting is distinct from thanatosis and may be an evolutionary strategy that complements other known defenses of the species, such as toxin secretion and defensive postures. Documenting this behavior is relevant for understanding antipredatory strategies in anurans.